Obedient daughter, silenced witch: the hysteric in Freudian psychoanalysis - Roux, Catharina (Rhodes University, Faculty of Humanities, Department of Psychology, 1989)
This study explores the theoretical consequences of Freud's renunciation of the seduction theory. The dissertation defends the thesis that the seduction theory was shaped as much by Freud's adherence to the nomonological model as by the empirical evidence of child sexual abuse. A renunciation of the seduction theory was inevitable, not because the accounts of the daughters were lies, but because the methodology was inappropriate. The nomonological model obscured the emotional structure of the nuclear family in which the structure itself, through which sexuality emerged, directed the girl's entrance into womanhood and caused the woman's dis-ease. Freud's methodology forced him to isolate an event as cause of an illness and to attribute the event to an agent. The universal perversity of the Victorian father thus became the central theme around which an explanation of a female disease was built. When this theme became theoretically untenable, Freud renounced the seduction theory and, still using the nomonological model, built up the construct of the Oedipus complex in which the father was vindicated. In order to exonerate the father, the transactions through which the child's libido developed were represented as originating in inherent tendencies. As a result, the hierarchical nature of the interaction between parent and child was distorted, and this led to the formulation of the distinction between real events and fantasies as a basic premise on which the difference between the pleasure principle and the reality principle rests. This formulation gave rise to the sharp duality between fantasy and reality which eventually compelled him to separate psychic reality and social reality. The theoretical structure built on this duality could not but fuse hysteria, masochism and "normal" femininity into an explanation of the female state, and obscure the essential social relations between men and women which were structured in terms of dominance and submission. The thesis traces the journey from the perverted father as cause of a female disease, hysteria, to the theoretical conjunction of masochism and hysteria. It comes to the conclusion that Freud's model is unable to explain the self-mutilation of the hysteric; nor is it capable of explaining the hysteric's refusal to participate in the circuit of symbolic exchanges which constituted Victorian society. The study further attempts to understand hysteria in terms of the complex interlacing of fact and fantasy and tries to show that fantasy was rooted in the facts of Victorian culture.
Keywords: Freud, Sigmund, 1856-1939 -- Criticism and interpretation; Hysteria; Psychoanalysis; Seduction